Pemanfaatan Satwa Liar sebagai Obat Tradisional di Desa Terak dan Teru, Kabupaten Bangka Tengah - Randi Syafutra; Fifin Fitriana; Abdul Kamal; Fika Wulandari; Nur Azizah Nawang Wulan; Zikri Alamsyah (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2021)
Terak and Teru Villages are two of the eleven villages surrounding Gunung Mangkol Grand Forest. Since a long time ago, the people in these villages have fulfilled their daily needs by utilizing the natural resources around Gunung Mangkol Grand Forest. One of the natural resources in the grand forest is wild animals commonly used as traditional medicine. This research was undertaken to find out what wild animals are used as traditional medicine by the people of Terak and Teru Villages; and to find out what parts are used, types of utilization, and processing methods of the wild animals. The research was conducted from November 1, 2021 to November 29, 2021. The research methods used were collecting data by surveys and selecting respondents using the snowball sampling technique. Selected respondents were then interviewed according to the questionnaire. Based on the research results, nine species of wild animals were used as traditional medicine by the people of Terak and Teru Villages. The parts of wild animals used were bile, liver, meat, and whole bodies. The types of use of wild animals were male stamina enhancer, asthma medicine, skin pain medicine, surgical wound medicine, malaria medicine, typhus medicine, cough medicine, toothache medicine, burn treatment, and headache medicine. The methods of processing wild animals were unprocessed, dried in the sun for the oil, roasted / burnt, and fried.